Performability evaluation of PROFIBUS-DP multi-master networks in relevant industrial scenarios - Carvalho, José Augusto (2010)
Network control systems operation strongly depends on the performance of the communication network. Therefore, their analysis becomes an important aspect to be considered, particularly in situations where network traffic has real-time constrains and the network operates in faulty environments. In this paper, a set of fault injection experi-ments were performed on a Profibus-DP network in order to assess the impact of faults in the network operation. The experiments reproduce typical industrial configurations with different network load conditions and fault scenarios. Based on the results of experiments the Profibus-DP bus cycle time, the message response time and the message worst case response time are assessed